2010
DOI: 10.1073/pnas.1005635107
|View full text |Cite
|
Sign up to set email alerts
|

Generating sparse and selective third-order responses in the olfactory system of the fly

Abstract: In the antennal lobe of Drosophila, information about odors is transferred from olfactory receptor neurons (ORNs) to projection neurons (PNs), which then send axons to neurons in the lateral horn of the protocerebrum (LHNs) and to Kenyon cells (KCs) in the mushroom body. The transformation from ORN to PN responses can be described by a normalization model similar to what has been used in modeling visually responsive neurons. We study the implications of this transformation for the generation of LHN and KC resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 36 publications
7
141
0
Order By: Relevance
“…4f ). As argued above, the model structure of leading-suppressive cells is probably generated by slow feedforward inhibition (Luo et al, 2010). The role of excitation and inhibition in shaping temporal filters and in decorrelating responses between cells in a population has been appreciated previously (Schmuker and Schneider, 2007;Wiechert et al, 2010;George et al, 2011).…”
Section: Population Sparsenessmentioning
confidence: 99%
“…4f ). As argued above, the model structure of leading-suppressive cells is probably generated by slow feedforward inhibition (Luo et al, 2010). The role of excitation and inhibition in shaping temporal filters and in decorrelating responses between cells in a population has been appreciated previously (Schmuker and Schneider, 2007;Wiechert et al, 2010;George et al, 2011).…”
Section: Population Sparsenessmentioning
confidence: 99%
“…Heptanal-induced inhibition of the MGC neurons through the LN network might thus synchronize MGC PNs and provide a more coincident input to upstream neurons in the mushroom bodies. There, the Kenyon cells are thought to need simultaneous input from several PNs, because they have been described as sparse coding cells in different insect species (Demmer and Kloppenburg, 2009;Ito et al, 2008;Jortner et al, 2007;Luo et al, 2010;Perez-Orive et al, 2002;Szyszka et al, 2005;Wang et al, 2004).…”
Section: Plant Odour Enhances the Response Contrast During Pulsed Phementioning
confidence: 99%
“…In terms of physiology, both the level of activity and the combination of activated mushroom body Kenyon cells varies, albeit slightly, with odor concentration. It will be interesting to see whether and which parameter set of biologically plausible mushroom body models (Luo et al 2010, Nehrkorn et al 2015 can account for both the high memory scores found when using a high odor concentration in training and in testing (Fig. 3A,B; Mishra et al 2013, loc.…”
Section: Synapsin Boosts Memory Strength For Highly Salient Eventsmentioning
confidence: 99%